2020
DOI: 10.1155/2020/7695276
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimental Research on Sealing Structure for a Retrievable Packer

Abstract: In order to reduce the failure accidents of conventional packers, a kind of sealing structure of retrievable packers is designed, which can provide reference for optimizing the sealing performance and pressure capacity of packers. And theoretical calculation and experimental research on their sealing performance and pressure capacity are carried out through the finite element analysis on the contact with large deformation based on Abaqus and experimental study. The results show that the upper packer is subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…This area contacts with the upregulating ring and the mantle ring, followed by the connection with the well wall or casing, forming a seal with the well wall or casing. As shown in Figure 1, plastic deformation will occur in the contact part between the indenter and the first rubber ring because of excessive stress and elastic deformation will be lost in the sealing process 30 . The chamfer position of the pressure ring and the support ring can lead to the protrusion of the rubber cylinder.…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This area contacts with the upregulating ring and the mantle ring, followed by the connection with the well wall or casing, forming a seal with the well wall or casing. As shown in Figure 1, plastic deformation will occur in the contact part between the indenter and the first rubber ring because of excessive stress and elastic deformation will be lost in the sealing process 30 . The chamfer position of the pressure ring and the support ring can lead to the protrusion of the rubber cylinder.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…As shown in Figure 1, plastic deformation will occur in the contact part between the indenter and the first rubber ring because of excessive stress and elastic deformation will be lost in the sealing process. 30 The chamfer position of the pressure ring and the support ring can lead to the protrusion of the rubber cylinder.…”
Section: Advantage and Sealing Mechanism Of Swellable Packermentioning
confidence: 99%
“…This can lead the packing elements to be seated in tension, compression or medium state (e.g. shear) with the potential to withstand pressure difference from top to bottom [37], and failure of the seals could result in pressure drop, leakage, and causes damage to the equipment and installation. Hu et al [31] found out that the stresses concentrated at the shoulder and inner vertex of the sealing ring can have a direct impact on the damage or failure (e.g., cracks and rupture, elastic failure, and extrusion) of the sealing ring under effective operational conditions.…”
Section: Loading and Sealing Effects On Hnbr For Wellhead Applicationmentioning
confidence: 99%
“…Achieving tightness with the least external load by sealers and improving their efficiency and determination of sealing parameters has an important scientific value. Some scholars have done relevant research on cylindrical sealers used in oil and gas production (Lan et al, 2019;Liu et al, 2020). Liu et al (2020) carried out theoretical calculation and experimental research through the finite element analysis on the contact with large deformation according to the design of the new seal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have done relevant research on cylindrical sealers used in oil and gas production (Lan et al, 2019;Liu et al, 2020). Liu et al (2020) carried out theoretical calculation and experimental research through the finite element analysis on the contact with large deformation according to the design of the new seal structure. Lan et al (2019) investigated the packer rubber with a conventional structure and optimized the materials and the structure of the packer rubber by ABAQUS software simulation and experimental research.…”
Section: Introductionmentioning
confidence: 99%